PERSEPSI GURU TERHADAP EFEKTIVITAS PENDEKATAN PEMBELAJARAN TERPADU DI SEKOLAH DASAR - Titin Sunaryati; Mega Alawiya; Galuh Arumsari; Tias Aprillia; Natasya Permata Putri; Ja’far Ridwanudin (STKIP Subang, 2025)
The integrated learning approach is considered appropriate for implementation at the elementary school level, as it aligns with children's developmental stages. However, the success of this approach greatly depends on teachers' perceptions as the primary implementers in the classroom. This study aims to analyze teachers' perceptions of the effectiveness of integrated learning in elementary schools. The method used is a literature review by examining scholarly sources, including academic journal articles and relevant educational literature. The analysis reveals that most teachers hold positive perceptions of integrated learning, recognizing its potential to enhance student engagement and facilitate cross-subject understanding. Nonetheless, its implementation faces several obstacles, such as limited instructional time, the complexity of authentic assessments, and a lack of adequate professional training. Teachers’ perceptions are shaped by practical experience, conceptual understanding, and institutional support. Therefore, improving the effectiveness of integrated learning requires strengthening teachers’ perceptions and competencies through ongoing training and collaborative professional development.